PERAN EXPERIENTIAL MARKETING, KUALITAS PELAYANAN DAN MOTIVASI BELANJA DALAM MEMPENGARUHI MINAT BELI ULANG - Selvi; Nuvriasari, Audita (Universitas Sarjanawiyata Tamansiswa, 2023)
This study aims to analyze the role of experiential marketing, service quality and shopping motivation in influencing repurchase intention at X Coffee & Eatery in Yogyakarta. The method used in this research is causal associative using a quantitative approach. Sampling was done by non-probability sampling method using a purposive sampling technique with a total of 100 respondents. The results showed that experiential marketing plays a positive and significant role in influencing repurchase intention, service quality does not play a significant role in influencing repurchase interest, shopping motivation plays a positive and significant role in influencing repurchase intention.